Analisis penerapan Standard Operating Procedure (SOP) sanitasi peralatan makan dengan angka kuman di Instalasi Gizi RSUD Meuraxa Banda Aceh - Israhul Maya; Abdul Hadi (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: the application of SOP is very important to pay attention to, because having SOP will help every job, where a hospital is a health service institution for many people it is so important to pay attention to the sanitation of its equipment. Improper sanitation can result in things that can be detrimental to patients such as poisoning, because food contamination can occur from various sources, one of which is cutlery that does not meet the requirements.Objective: to find out the application of the SOP for sanitation of cutlery with germ numbers in the Nutrition Installation of Meuraxa Hospital, Banda Aceh.Methods: the design used in this research is quasi-experimental with one group pretest posttest design. This research was conducted on 20 June-26 August 2022 at the Meuraxa Hospital in Banda Aceh. A sample of 9 servers was taken by saturated sampling technique. Data processing through four stages, namely editing, coding, processing, tabulating. Data analysis used the Dependent T-test.Results: there is a difference in the behaviour of the servers before the socialization and after the socialization regarding the implementation of the SOP for eating utensils sanitation (p= 0.002). The value of the germ count on cutlery before being given socialization regarding SOP for sanitation of cutlery obtained an average laboratory result of 275.67 colonies/cm2 and there was a decrease in laboratory results of the germ count after socialization to 77.56 colonies/cm2, 0.023.Conclusion: there is a significant difference in implementing of the SOP for the sanitation of cutlery with the number of germs in the Nutrition Installation of the Meuraxa Hospital in Banda Aceh. Conduct further research with different designs to find out more about what factors can affect the number of germs on cutlery.